1977
DOI: 10.1007/bf02655163
|View full text |Cite
|
Sign up to set email alerts
|

The properties and performance of poly AO™‐79; A nonabsorbable, polymeric antioxidant intended for use in foods

Abstract: AND SUMMARYThe physical, chemical, and biological characteristics of Poly AOTM-79, a composition selected from a class of polymers prepared by the polycondensation of divinylbenzene and a blend of various sterically hindered phenols and hydroquinone, are discussed. Data are presented indicating that Poly AOTM-79 demonstrates excellent antioxidant activity in stabilizing vegetable oils when compared to monomeric food grade antioxidants [butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), and tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
3
0
1
Order By: Relevance
“…Chemical characteristics of the oxidative fluorescence-producing reaction on polyamide powder have been discussed (Porter, 1983). Some of the evidence is superficially consistent with but not sufficient to establish the involvement of vapor and Sherwin, 1966 POLY cottonseed / soybean oil blend Furia and Bellanca, 1977 "Abbreviations correspond to the text and Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical characteristics of the oxidative fluorescence-producing reaction on polyamide powder have been discussed (Porter, 1983). Some of the evidence is superficially consistent with but not sufficient to establish the involvement of vapor and Sherwin, 1966 POLY cottonseed / soybean oil blend Furia and Bellanca, 1977 "Abbreviations correspond to the text and Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…Recently attention has been focused on the amount of phenolic antioxidants remaining unchanged or retained by the oil after deep-fat frying. This varied widely, i.e., 1-85 % of the original substrate, depending on the stability of the antioxidant, techniques employed, and frying conditions (Furia and Bellanca, 1977;Lin et al, 1981; Fritsch, 1981; Stevenson et al, 1984; Warner et al, 1986;Kim and Pratt, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the disappearance of the parent antioxidant, the use of antioxidants in frying oil does yield a food product with a longer shelf life than the identical product fried in antioxidant-free oil (Min and Schweizer, 1983; Augustin and Berry, 1984). In a study with radiocarbon-labeled 2-(1,1-dimethylethyl) -1,4benzenediol (TBHQ), Furia and Bellanca (1977) showed that the radiocarbon taken up by the potato was 80-85% of the expected level based upon the quantity of absorbed fat. Leventhal et al (1976) isolated and identified a stilbenequinone derivative of BHT from vegetable oils heated at 190 °C for 11 days.…”
mentioning
confidence: 99%